Two decades of genetic profiling yields first evidence of natal philopatry and long‐term fidelity to parturition sites in sharks. Issue 1 (9th December 2013) - Feldheim, Kevin A.; Gruber, Samuel H.; DiBattista, Joseph D.; Babcock, Elizabeth A.; Kessel, Steven T.; Hendry, Andrew P.; Pikitch, Ellen K.; Ashley, Mary V.; Chapman, Demian D.
Abstract Sharks are a globally threatened group of marine fishes that often breed in their natal region of origin. There has even been speculation that female sharks return to their exact birthplace to breed ('natal philopatry'), which would have important conservation implications. Genetic profiling of lemon sharks (Negaprion brevirostris) from 20 consecutive cohorts (1993–2012) at Bimini, Bahamas, showed that certain females faithfully gave birth at this site for nearly two decades. At least six females born in the 1993–1997 cohorts returned to give birth 14–17 years later, providing the first direct evidence of natal philopatry in the chondrichthyans. Long‐term fidelity to specific nursery sites coupled with natal philopatry highlights the merits of emerging spatial and local conservation efforts for these threatened predators.